Personalised nitinol stent for focal plaques: Design and evaluation. (January 2022) - He, Ran; Zhao, Liguo; Silberschmidt, Vadim V.; Feng, Jiling; Serracino-Inglott, Ferdinand
Abstract: The purpose of this study is to develop personalised nitinol stents for arteries with one and two opposite focal plaques. Novel designs are evaluated through comparison with a commercial stent design, in terms of lumen gain and shape as well as stress levels in the media layer after stenting. Methods: Personalised stents are developed for arteries with one and two opposite focal plaques, based on medical imaging of patients and computer simulations. In silico analysis is then carried out for assessment of stent performance in the diseased arteries. Results: Personalised designs significantly increase the lumen gain, reduce the stresses in the media layer, and improve the lumen shape compared to the commercial nitinol stent. Conclusion: The personalised designs show outstanding performance compared to the commercial stent. Significance: This pilot study proves that personalised nitinol stents are able to deliver desirable treatment outcomes.